Program Gemarsari sebagai pencegahan hipertensi pada dewasa dan lansia di kelurahan kertosari - Prawira, Tantra Dipta; Arfiani, Novi Dian; Putri Naswa, Auxilya Cahaya; Rizkiana, Claradea; Putri Anggriyanto, Nastiti Ivory; Anggraeni, Jasmine Sukma (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Hypertension is a non-communicable disease (NCD) with a high prevalence and remains a major health problem in Kertosari Village, Ponorogo Regency. According to the 2024 Ponkesdes report, hypertension is recorded as the most common case, indicating the need for simple and community-acceptable promotive and preventive efforts. To address this issue, the Gemarsari Program: Gerakan Masyarakat Kertosari Sehat dan Mandiri was implemented, focusing on increasing physical activity and raising community awareness in hypertension prevention. The activities included blood pressure measurement, 30 minutes of healthy exercise, and a follow-up blood pressure check after physical activity. The program was conducted on January 22 and 29, 2025, at the Kertosari Village Hall with 34 participants. Data were analyzed descriptively and quantitatively by comparing the mean blood pressure before and after the exercise. The results showed a reduction in average blood pressure from 139.44 mmHg to 135.15 mmHg. Thus, the Gemarsari Program proved effective as a simple community-based intervention to reduce blood pressure and promote a healthier lifestyle.